Ex-ante impact of on-farm diversification and forward integration on agricultural value chain resilience: A system dynamics approach - Aboah, J.; Wilson, M.J.W.; Bicknell, K.; Rich, Karl M. (Elsevier, 2021)
Objective This paper examines the ex-ante impacts of on-farm diversification and forward integration strategies on agricultural value chain resilience, with an empirical focus on Ghana’s cocoa value chain. Method System dynamics modelling was used to explore five scenarios involving variable-input on-farm diversification pursued by cocoa farmers in Ghana and the simultaneous adoption of forward integration strategies by Ghana and Cote d’Ivoire. Results and Conclusions An adaptive strategy involving the simultaneous pursuit of variable-input on-farm diversification and a cooperative forward integration strategy by both Ghana and Cote d’Ivoire was found to result in the highest level of resilience. Under such an adaptive strategy, in-country processors will be the most impacted when the level of safety stocks are below 25% of the average stock level during the period of losses in raw material production. Significance The findings suggest that a policy direction that supports on-farm diversification and in-country processing enhances the aggregate resilience of the cocoa value chain, irrespective of the forward integration strategy adopted by Cote d’Ivoire.